Peran Penapisan Morfologi Matematik terhadap Kenampakan Linier pada Citra Landsat TM = The Role of Mathematical Morphology Filtering to Linier Features at Landsat TM Image - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
The aim of this research is to study the capability of mathematical morphology filtering to enhance linier features recorded in the landsat TM Image. Digital data of the channel 4 landsat TM Image was used to study linier features in a part of Kulonprogo regency, the spacial province of Yogyakarta, with the spacial reference to street and river. Filtering technique was studied with a member of mathematical morphology filtering acquired by combination technique between morphology filters, combination between morphology filters with the original image, and combination between morphology filters with derivation one, combination filters in this study was carried out by applying arithmatic operation and caecade filtering using ENVI 3.2. The result of this study indicated that the combination between dilation filter and the original image produced linier features more clearly observable with thick and sharp edge, as compared to the Roberts filter on a template of 3 x 3 size. It can be concluded that the capability of combination mathematical morphology filters are better than the derivation filters for the enhancement of linier features on landsat TM Image.